2018
DOI: 10.1002/ldr.3164
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grazing exclusion on soil–vegetation relationships in a semiarid grassland on the Loess Plateau, China

Abstract: Grazing exclusion (GE) is regarded as an effective practice to restore degraded grasslands. However, the patterns of vegetation recovery and related regulating factors in response to fencing have not been fully recognized. Hence, quantitative analysis of vegetation-soil relationships in response to GE was conducted in a semiarid grassland located on the Loess Plateau, North China. The results revealed that enclosure establishment significantly increased vegetation cover, height, and productivity but reduced pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 62 publications
1
14
1
Order By: Relevance
“…AGB exhibited a significant decreasing trend with an increase in GI in most grassland regions of northern China [16,23,[55][56][57] and the world [10]. The percentage reduction of AGB in our study area (13.24% in July at a GI of 0.5 goats/ha) was lower than the proportional reduction 47.86% from other site of Loess Plateau [25,58], 42.77% from 251 data sets in China [16], and 23% from 236 data sets around the world [10].…”
Section: Response Of Agb To Grazingcontrasting
confidence: 52%
“…AGB exhibited a significant decreasing trend with an increase in GI in most grassland regions of northern China [16,23,[55][56][57] and the world [10]. The percentage reduction of AGB in our study area (13.24% in July at a GI of 0.5 goats/ha) was lower than the proportional reduction 47.86% from other site of Loess Plateau [25,58], 42.77% from 251 data sets in China [16], and 23% from 236 data sets around the world [10].…”
Section: Response Of Agb To Grazingcontrasting
confidence: 52%
“…This could be attributed to the fact that the increase in soil density made the soil have less water-holding capacity, and the resulting water deficit inhibited the plant growth. Soil pH is regarded as the main factor regulating species diversity [58]; in our case study, it was also an important factor controlling plant community characteristics. A positive correlation between soil pH and plant diversity appeared in the LLG coal mine, while the opposite result was found in the WLHD and JZT coal mines.…”
Section: Interaction Between Plant Community Characteristics and Soilmentioning
confidence: 90%
“…Compared with the SMC of other restoration sites, it was found that the SMC of newly reclaimed soil (RA18) was not the lowest because of the artificial irrigation after restoration. Over time, the water retention ability gradually increased, owing to improvements in soil structure [58]. Because of the frequent movements of heavy machinery excavating and replacing topsoil material in the restoration process, the reclaimed mine soils are highly compact, leading to high soil bulk density.…”
Section: Effects Of Mining and Restoration On Soil Properties And Plamentioning
confidence: 99%
“…About 90% of the natural grasslands in China has been degraded due to reclamation and overgrazing (Gang et al, ; Nan, ). Livestock exclosure and nutrient fertilization are effective and widely used ways to restore the degraded grasslands (Bai et al, ; Ren et al, ). In the past decades, our mechanistic understanding of the restoration of plant community composition and production following those restoration strategies has been substantially improved by empirical studies from diverse grassland ecosystems (Baer, Blair, Collins, & Knapp, ; Bai et al, ; Chen et al, ).…”
Section: Introductionmentioning
confidence: 99%